Evidence for Widespread Inter‐Basin Vicariance of Fishes Associated With Quiescent Geologic Features in the Southeastern United States - Bryson G. Hilburn; Byron J. Freeman; Eric J. Walther; Mary C. Freeman; David S. Leigh; John P. Wares (Journal of Biogeography, 2026)
Aim Stream captures are implicated as drivers of speciation in many groups of lotic fishes. In the southeastern United States, numerous stream‐dwelling animals possess restricted trans‐divide populations at localities where quiescent geologic features intersect drainage divides, suggesting potential evidence for inter‐basin vicariance via stream capture. However, there has not yet been a comprehensive quantitative biogeographical analysis of these patterns. Herein, we present evidence for widespread patterns of evolutionarily recent inter‐basin vicariant events across major geologic structures that have been tectonically dormant for many millions of years. Location Southeastern North America. Taxon Freshwater fishes. Methods We used Kriging spatial interpolation analysis on a dataset of 5434 sample sites (~188,000 species‐specific distribution records) that included ~375 fish species to visualise patterns of aberrant fish distribution records across highland physiographic regions of Alabama, Georgia, Tennessee, and the Carolinas (USA). These patterns were further explored with a comprehensive synthesis of published fish distribution maps and museum records. We collected cytochrome‐ b sequence data from 337 individual fish of 14 representative ‘transferred’ species (20 intraspecies population pairs) from ~11 paired localities across the Brevard Fault, Allatoona Fault, and Blue Ridge Escarpment implicated in inter‐basin captures to estimate coarse timing of vicariant events and to infer distributional artefacts caused by anthropogenic introduction. Results A heatmap generated from Kriging analysis shows a concentration of aberrant distributional records of fishes around the Brevard Fault Zone and the Blue Ridge Escarpment and other more minor quiescent geologic features. Our synthesis of museum records and fish distribution literature revealed documented evidence of a total of 115 species‐transfer incidences (52 taxa) that exhibit inter‐basin transfer along these features. Of the 20 intraspecies population pairs examined for genetic diversity, measures of Φ ST and associated AMOVA p ‐values indicate significant levels of genetic divergence for 13. Main Conclusions Large‐scale, quiescent geologic structures appear to drive localised vicariant events via stream capture through fostering differential erosional rates of captor and victim tributaries. Stream capture emerges as a prevalent process underlying inter‐basin range expansion and diversification of aquatic animals in upland regions.

Accumulation of microbial hazards and assessment of food hygiene associated with broiler chicken processing at open air food markets in Maputo, Mozambique - Frederica Lamar; Amélia Mondlane-Milisse; Denise R.A. Brito; Hermógenes N. Mucache; Kelsey J. Jesser; Christine S. Fagnant-Sperati; Courtney Victor; Kayoko Shioda; José M. Fafetine; Joaquim Ângelo Osvaldo Saíde; Eric M. Fèvre; Mia Catharine Mattioli; et al. (International Journal of Food Microbiology, 2025)

Comparison of the reinforcing, antinociceptive, and respiratory depressant effects of prototypical and G-protein biased mu-opioid receptor agonists in male and female Sprague–Dawley rats - C. Austin Zamarripa; Tanya Pareek; Loc M. Pham; Bruce E. Blough; Hayley M. Schrock; Eric J. Vallender; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2024)

A new approach methodology using kinetically-derived maximum dose levels in risk assessment – A case study with afidopyropen - Anne E. Loccisano; Elaine Freeman; Adriana Doi; Markus Frericks; Ivana Fegert; Eric Fabian; Brandy Riffle (Regulatory Toxicology and Pharmacology, 2023)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

The International Comprehensive Ocean-Atmosphere Data Set – Meeting Users Needs and Future Priorities - Eric Freeman; Elizabeth C. Kent; Philip Brohan; Thomas Cram; Lydia Gates; Boyin Huang; Chunying Liu; Shawn R. Smith; Steven J. Worley; Huai-Min Zhang (Frontiers in Marine Science, 2019)

Tracking progress in marine climatology - Sergey Gulev; Eric Freeman (International Journal of Climatology, 2017)

ICOADS Release 3.0: a major update to the historical marine climate record - Eric Freeman; Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Elizabeth C. Kent; William E. Angel; David I. Berry; Philip Brohan; Ryan Eastman; Lydia Gates; Wolfgang Gloeden; Zaihua Ji; et al. (International Journal of Climatology, 2017)
We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set ( ICOADS ) in the latest Release 3.0 ( R3 .0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3 .0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS , reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS ' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced ‘preliminary’ monthly data and product extensions past 2014, R3 .0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.

ICOADS Release 2.5: extensions and enhancements to the surface marine meteorological archive - Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Zaihua Ji; J. Eric Freeman; David I. Berry; Philip Brohan; Elizabeth C. Kent; Richard W. Reynolds; Shawn R. Smith; Clive Wilkinson (International Journal of Climatology, 2011)
Release 2.5 of the International Comprehensive Ocean‐Atmosphere Data Set (ICOADS) is a major update (covering 1662–2007) of the world's most extensive surface marine meteorological data collection. Building on extensive national and international partnerships, many new and improved contributing datasets have been processed into a uniform format and combined with the previous Release 2.4. The new data range from early non‐instrumental ship observations to measurements initiated in the twentieth century from buoys and other automated platform types. Improvements to existing data include replacing preliminary Global Telecommunication System (GTS) receipts with more reliable, delayed mode reports for post‐1997 data, and in the processing and quality control (QC) of humidity observations. Over the entire period of record, spatial and temporal coverage has been enriched and data and metadata quality has been improved. Along with the observations, now updated monthly in near real time, Release 2.5 includes quality‐controlled monthly summary products for 2° latitude × 2° longitude (since 1800) and 1° × 1° boxes (since 1960), together with multiple options for access to the data and products. The measured and estimated data in Release 2.5 are subject to many technical changes, multiple archive sources, and historical events throughout the more than three‐century record. Some of these data characteristics are highlighted, including known unresolved errors and inhomogeneities, which may impact climate and other research applications. Anticipated future directions for ICOADS aim to continue adding scientific value to the observations, products, and metadata, as well as strengthen the cooperative enterprise through expanded linkages to international initiatives and organisations. Copyright © 2010 Royal Meteorological Society

Recovery of logbooks and international marine data: the RECLAIM project - Clive Wilkinson; Scott D. Woodruff; Philip Brohan; Stefan Claesson; Eric Freeman; Frits Koek; Sandra J. Lubker; Catherine Marzin; Dennis Wheeler (International Journal of Climatology, 2011)
The RECovery of Logbooks and International Marine data (RECLAIM) project is a concerted, international effort to facilitate and encourage the recovery—through imaging and digitisation—of archived marine weather observations, platform and instrumental metadata and historical documentation, from many different countries. Non‐instrumental observations of wind and weather have been recorded in ships' logbooks for hundreds of years, augmented by systematic instrumental observations of sea surface and air temperatures, barometric pressure and other meteorological (and oceanographic) elements largely since the mid‐nineteenth century. Once digitised, these data are widely useful for climate studies and other avenues of scientific research—including oceanography, fisheries, maritime history and ecology—thus improvements seeking to address gaps and weaknesses in the currently available data record can be of major importance. In addition to documenting and prioritising archived ship logbook records for imaging and digitisation in support of that goal, RECLAIM provides expert assistance in the interpretation of historical marine records in relation to navigation, observational practices and recording. Since the project inception in 2005, RECLAIM has facilitated, for example, recovery of logbooks of the Dutch and English East India Companies in the nineteenth century, and of the British Royal Navy of the twentieth century. Currently the project website includes reference lists, rescued UK and US marine documents, extensive UK archive reports and detailed inventories of ship movements. A variety of other developing international linkages are discussed, including to Chilean, Dutch, French, German, Finnish, Norwegian, Swedish and US historical records. © Royal Meteorological Society and Crown Copyright 2010.

The role of eriophyoids in fungal pathogen epidemiology, mere association or true interaction? - Efrat Gamliel-Atinsky; Stanley Freeman; Marcel Maymon; Eduard Belausov; Ronald Ochoa; Gary Bauchan; Anna Skoracka; Jorge Peña; Eric Palevsky (Experimental and Applied Acarology, 2010)

Population studies and conservation of Jamaica’s endangered swallowtail butterfly Papilio (Pterourus) homerus - Eric Garraway; A. J. A. Bailey; B. E. Freeman; J. R. Parnell; T. C. Emmel (Journal of Insect Conservation, 2008)

Microsatellite primers indicate the presence of asexual populations ofVenturia inaequalis in coastal Israeli apple orchards - Eric W. A. Boehm; S. Freeman; E. Shabi; T. J. Michailides (Phytoparasitica, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)